Secondary Pulmonary Hypertension and Right-Sided Heart Failure at Presentation in Grave’s Disease - Swapnil Panjabrao Ganeshpure; Gaurang Nandkishor Vaidya; Vipul Gattani (Case Reports in Endocrinology)
A young female presented with evidence of right-sided heart failure and was subsequently found to have significant pulmonary artery hypertension (PAH). Because of her normal left ventricular function and pulmonary capillary wedge pressure, the most probable site of etiology seemed to be the pulmonary vasculature. All the common possible secondary causes of PAH were ruled out, but during the investigations, she was found to have elevated thyroid function tests compatible with the diagnosis of Grave’s disease. The treatment of Grave’s disease, initially by medications and subsequently by radioiodine therapy, was associated with a significant reduction in the pulmonary artery systolic pressure. The purpose of this case report is to highlight one of the unusual and underdiagnosed presentations of Grave’s disease.